Independent Thinking and Hard Working, or Caring and Well Behaved? Short- and Long-Term Impacts of Gender Identity Norms - Núria Rodríguez-Planas; Anna Sanz-de-Galdeano; Anastasia Terskaya (Institute of Labor Economics (IZA), 2018)
Using the National Longitudinal Study of Adolescent to Adult Health, we explore the causal effect of gender-identity norms on female teenagers' engagement in risky behaviors relative to boys in the US. To do so, we exploit idiosyncratic variation across adjacent grades within schools in the proportion of high-school peers' mothers who think that important skills for both boys and girls to possess are traditionally masculine ones, such as to think for him or herself or work hard, as opposed to traditionally feminine ones, namely to be well-behaved, popular or help others. We find that a higher proportion of mothers who believe that independent thinking and working hard matter for either gender reduces the gender gap in risky behaviors, traditionally more prevalent among males, both in the short and medium run. We also find evidence of convergence in the labor market in early adulthood. Short- and medium-run results are driven by a reduction in males' engagement in risky behaviors; long-run results are driven by females' higher annual earnings and lower welfare dependency.
Keywords: I10; I12; J15; J16; J22; Z13; 330; gender-identity norms; short-; medium- and long-run effects; risky behaviors and labor market outcomes; Add Health